Negotiating Culture : Heritage, Ownership, and Intellectual Property - La Follette, Laetitia Amelia (Book collections on Project MUSE., 2013)
"Rival claims of ownership or control over various aspects of culture are a regular feature of our twenty-first-century world. Such debates are shaping disciplines as diverse as anthropology and archaeology, art history and museum studies, linguistics and genetics. This provocative collection of essays--a series of case studies in cultural ownership by scholars from a range of fields--explores issues of cultural heritage and intellectual property in a variety of contexts, from contests over tangible artifacts as well as more abstract forms of culture such as language and oral traditions to current studies of DNA and genes that combine nature and culture, and even new, nonproprietary models for the sharing of digital technologies. Each chapter sets the debate in its historical and disciplinary context and suggests how the approaches to these issues are changing or should change. One of the most innovative aspects of the volume is the way each author recognizes the social dimensions of group ownership and demonstrates the need for negotiation and new models. The collection as a whole thus challenges the reader to reevaluate traditional ways of thinking about cultural ownership and to examine the broader social contexts within which negotiation over the ownership of culture is taking place."--Publisher's description